2021
DOI: 10.1029/2021gl095560
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Volatile Organic Compounds During the COVID‐19 Lockdown in Changzhou, China

Abstract: To contain the spread of coronavirus disease (COVID-19), many countries underwent large-scale lockdowns in 2020. Decreases in vehicle traffic, industrial activity, and power consumption led to reduced emissions of air pollutants and greenhouse gases. For example, reductions in nitrogen dioxide columns were detected over Asia, Europe and North America by space-based instruments (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…A result was unprecedented decreases in Northern Hemisphere (NH) pollution including important ozone precursors nitrogen oxides (NO x = nitric oxide [NO] + nitrogen dioxide [NO 2 ]) and Volatile Organic Compounds (VOCs). The decreases in pollution and subsequent changes in tropospheric ozone, particularly in the NH, has led to a large number of published articles on this subject (e.g., Bauwens et al., 2020 ; Bouarar et al., 2021 ; Bray et al., 2021 ; Campbell et al., 2021 ; Elshorbany et al., 2021 ; Jensen et al., 2021 ; Keller et al., 2021 ; Liu et al., 2020 ; Miyazaki et al., 2021 ; Pakkattil et al., 2021 ; Sicard et al., 2020 ; Stavrakou et al., 2021 ; Steinbrecht et al., 2021 ). These studies have shown numerous cases of large reductions in NO 2 , VOCs, and other pollutants in the troposphere including free‐tropospheric ozone during spring‐summer 2020 that reached 5%–10% deficits or greater throughout the NH, particularly in urban environments.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A result was unprecedented decreases in Northern Hemisphere (NH) pollution including important ozone precursors nitrogen oxides (NO x = nitric oxide [NO] + nitrogen dioxide [NO 2 ]) and Volatile Organic Compounds (VOCs). The decreases in pollution and subsequent changes in tropospheric ozone, particularly in the NH, has led to a large number of published articles on this subject (e.g., Bauwens et al., 2020 ; Bouarar et al., 2021 ; Bray et al., 2021 ; Campbell et al., 2021 ; Elshorbany et al., 2021 ; Jensen et al., 2021 ; Keller et al., 2021 ; Liu et al., 2020 ; Miyazaki et al., 2021 ; Pakkattil et al., 2021 ; Sicard et al., 2020 ; Stavrakou et al., 2021 ; Steinbrecht et al., 2021 ). These studies have shown numerous cases of large reductions in NO 2 , VOCs, and other pollutants in the troposphere including free‐tropospheric ozone during spring‐summer 2020 that reached 5%–10% deficits or greater throughout the NH, particularly in urban environments.…”
Section: Introductionmentioning
confidence: 99%
“…Jensen et al. ( 2021 ) identified pollution reductions of 40%–60% for industry and about 70% for traffic over China in early 2020 using TROPOMI and ground‐based measurements. Miyazaki et al.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations